Remarkable desmid species from the southern Patagonian highlands - Coesel, Peter F. M. (2017)
Phytoplankton research in a number of shallow lakes in southern Patagonia revealed the occurrence of three noteworthy Cosmarium species. One of them, Cosmarium decussare Brook et Williamson, found only once before in Antarctica, is remarkable for its highly asymmetric cell morphology. The other two species, Cosmarium chapuense and Cosmarium mickeyoides, striking by an unusual cell shape, are described as new to science. Ecological and biogeographical characteristics are discussed.